Exploring The Pedagogical Flow Of Chinese Primary School Mathematics Lessons Before, During And After Lesson Study - Chia, Hui Min (2014)
This study explored and compared the pedagogical flow of Chinese primary school mathematics lessons before, during and after the implementation of Lesson Study (LS) process. The pedagogical flow refers to the teaching and learning process in a classroom while LS is a Japanese model of teacher professional development. This study employed a qualitative case study research design. There were three mathematics LS groups from three project schools with a total of 15 mathematics teachers participated in this study. Multiple sources of qualitative data were collected: 15 lesson observations, nine group discussions, three individual teacher interviews and various artefacts collected during the lessons. Based on the framework of Activity Theory, the data was categorised into teacher’s activities, pupils’ activities, and the usage of classroom resources. The findings showed that the pedagogical flow of the lesson before the implementation of LS was mainly characterised by passive individual pupil seatwork and teachers giving random examples and exercises. However, the pedagogical flow of lessons during and after the implementation of LS geared toward more active pupils’ learning and teachers used more variety of classroom resources. These findings imply that LS process has the potential in enhancing the teacher’s pedagogical practices. Nevertheless, in this study, only three LS cycles were implemented, thus, the improvement in pedagogical practices was still limited. In fact, the upkeep of this improvement depends very much on the sustainability of the LS implementation which remains a challenge.